The influence of SARS‐CoV‐2 vaccination on post‐operative outcomes in microsurgery patients. Issue 7 (15th July 2022) - Taghioff, Susan M.; Slavin, Benjamin R.; Narasimman, Manish; Samaha, Georges; Samaha, Mario; Holton, Tripp; Singh, Devinder
Abstract: Background: The healthcare industry's efforts to immunize the global community against severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) have been unprecedented. Given the fast‐tracking of the novel vaccine, its short‐ and long‐term medical implications remain largely to‐be‐determined in most patient populations. This study aims to analyze 90‐day post‐operative outcomes in microsurgical patients, who have received or not received SARS‐CoV‐2‐vaccination, using a continuously updated federated electronic medical record network (TriNetX Inc, Cambridge, MA). Methods: After screening 70 million de‐identified records, 16, 799 microsurgery patients aged 18–99 meeting medical coding criteria were allocated into two cohorts. Cohort One received SARS‐CoV‐2‐vaccination prior to undergoing microsurgery whereas Cohort Two did not. Two equally sized cohorts, totaling 818 patients were created after propensity score matching for characteristics including: age, race, ethnicity, smoking, hypertension, heart disease, diabetes, obesity, chronic obstructive pulmonary disease, and history of SARS‐CoV‐2 exposure. Postoperative outcomes within 30‐, 60‐, and 90‐days of microsurgery were analyzed. Results: Patients who were SARS‐CoV‐2‐immunized experienced significantly lower ( p < .01) surgical site infections (Absolute Risk Reduction (ARR)[95%CI]) = (3.79%–5.36% [0.84–8.54]) ICU admission (9.47%–9.82%[5.45–13.88]), generalized infections (7.68%–9.92%[3.15–14.64]), and hospitalizations (28.48%–32.57%[20.99–40.13]) within 30‐, 60‐, and 90‐days of microsurgery. Additionally, SARS‐CoV‐2‐vaccinated patients also experienced significantly less flap failure (2.49%[0.97–4.02]) and death (2.46%[0.96–3.97]) within 30‐ and 60‐days post‐operatively. Conclusion: Our analysis examines the potential protective effect of SARS‐CoV‐2‐vaccination in microsurgical patients. Limitations include the retrospective nature of this analysis and the inherent reliance on medical coding. Future prospective studies are warranted to better understand if in fact pre‐operative SARS‐CoV‐2‐vaccination has the potential to protect against post‐operative microsurgery outcomes.